The relationship between IL-4 polymorphisms and asthma: a systematic review - Silva, Marcos Jessé Abrahão; Monteiro, Ellerson Oliveira Loureiro; e Silva, Bianca Benicio; Martins, Debora Zoila da Conceição; Siqueira, Andrei Santos; Santana, Bárbara Brasil (Revista do Instituto Adolfo Lutz, 2022)
Asthma is a chronic and heterogeneous disease of the airways that begins in childhood and persists, in many cases, into adulthood. The disease is the result of environmental, epigenetic and genetic interactions. This work aims to review the polymorphisms described in the literature in the IL-4 gene associated with susceptibility or protection to the development of asthma. This is a systematic literature review, carried out in PubMed, MEDLINE and Science Direct databases in the time frame from 2000 to July 2021, revealing the following key points: IL-4, Polymorphisms and Asthma. The search resulted in 29 articles, all in English. Despite some divergent studies, the SNP rs2243250, which was the most studied in populations from different countries, was also the one that found the most correlations of susceptibility with the disease. It is concluded that although there is controversial data on IL-4 SNPs related to the disease, the association of pangenomic studies has brought a list of genes and their variations associated with the risk of developing asthma, such as the rs2243250 SNP that was well related in populations of several countries analyzed.